Perkembangan Terkini Penggunaan Resistivitas Geolistrik Untuk Survei Longsor : Sebuah Tinjauan - Selly Feranie; Adinda Pramesti Wahyuning Putri; Amata Kara Perdani Handiman; Adrin Tohari (Universitas Sultan Ageng Tirtayasa, 2023)
The peak of the rainy season in 2022/2023 has caused many disasters, especially landslides in Indonesia, which have claimed many victims and caused damage to settlements and infrastructure. Various geophysical methods have been widely applied to identify slip fields. In addition, geophysical methods are used to determine the type and characteristics of landslides. The slip field has a lithology of 2 subsurface layers of soil or contrasting rocks, namely soft and hard soil layers. Therefore, one of the geophysical methods that is effective in identifying slip planes is the geoelectric method because of the stark contrast in resistivity in the two soil layers. This article will review research that uses geoelectric data to survey landslide potential in the last ten years. In addition, this article also reviews the latest research related to geoelectricity, namely Time-Lapse Electrical Resistivity Tomography (TL-ERT), starting from studies that have used this method and the potential and direction of using this method in the future.